A música enquanto instrumento de comunicação terapêutica na criança hospitalizada - Carapau, Filipa Alexandra da Costa Carvalho; Silva, Joana Rafaela Eleutério Reis da; Rocha, Graça Moraes da (Revista Recien - Revista Científica de Enfermagem, 2024)
A experiência traumática vivida pela criança e família em contexto de hospitalização pode ser minimizada com a utilização da música como uma estratégia comunicacional com impacto no seu conforto e bem-estar. O estudo tem como objetivo demonstrar o benefício da música enquanto instrumento de comunicação terapêutica na criança hospitalizada, para a prática de enfermagem. Este artigo baseia-se numa revisão da literatura, tendo por base artigos científicos das bases de dados CINAHL Complete, MEDLINE Complete, Mediclatina, Nursing & Allied Health Collection: Comprehensivee Cochrane Database of Systematic Reviews com limite temporal de 2017 até 2023. Destaca-se a intervenção do enfermeiro na utilização da música como estratégia promotora de bem-estar, socialização e redução da dor podendo ser considerada como intervenção incluída no plano de saúde. Descritores: Música, Enfermagem, Criança, Hospital. Music as an instrument of therapeutic communication in hospitalized children Abstract: The traumatic experience experienced by the child and family in the context of hospitalization can be minimized by using music as a strategy of communication which impacts their comfort and well-being. This study aims to show the benefits of the music as a therapeutic communication instrument for hospitalized children, in nurse practice. This article is based in reviewing the current literature by taking into account scientific articles from the databases CINAHL Complete, MEDLINE Complete, Mediclatina, Nursing & Allied Health Collection: Comprehensivee Cochrane Database of Systematic Reviews ranging from 2017 to 2023. Here we highlight the nurse intervention in the usage of music as strategy that promotes well-being, socialization and pain reduction that can be included as an intervention in the health plan. Descriptors: Music, Nursing, Child, Hospital. La música como instrumento de comunicación terapéutica en niños hospitalizados Resumen: La experiencia traumática vivida por el niño y la familia en el contexto de hospitalización puede ser minimizada con el uso de la música como una estrategia comunicativa con impacto en su confort y bienestar. El estudio tiene como objetivo demostrar el beneficio de la música como instrumento de comunicación terapéutica en el niño hospitalizado, para la práctica de enfermería. Este artículo se basa en una revisión de la literatura, utilizando artículos científicos de las bases de datos CINAHL Complete, MEDLINE Complete, Mediclatina, Nursing & Allied Health Collection: Comprehensive y Cochrane Database of Systematic Reviews con un límite temporal de 2017 hasta 2023. Se destaca la intervención del enfermero en el uso de la música como estrategia promotora de bienestar, socialización y reducción del dolor, pudiendo ser considerada como una intervención incluida en el plan de salud. Descriptores: Música, Enfermería, Niño, Hospital.